Vaccine development: From concept to early clinical testing. Issue 52 (20th December 2016) - Cunningham, Anthony L.; Garçon, Nathalie; Leo, Oberdan; Friedland, Leonard R.; Strugnell, Richard; Laupèze, Béatrice; Doherty, Mark; Stern, Peter
Highlights: Detailed knowledge of the pathogen is a pre-requisite for antigen selection. Disease epidemiology and clinical manifestations influence vaccine requirements. Increasing knowledge and new technologies drive innovative vaccine design. Manufacture and delivery of vaccine antigens must be practicably achievable. Abstract: In the 21st century, an array of microbiological and molecular allow antigens for new vaccines to be specifically identified, designed, produced and delivered with the aim of optimising the induction of a protective immune response against a well-defined immunogen. New knowledge about the functioning of the immune system and host pathogen interactions has stimulated the rational design of vaccines. The design toolbox includes vaccines made from whole pathogens, protein subunits, polysaccharides, pathogen-like particles, use of viral/bacterial vectors, plus adjuvants and conjugation technology to increase and broaden the immune response. Processes such as recombinant DNA technology can simplify the complexity of manufacturing and facilitate consistent production of large quantities of antigen. Any new vaccine development is greatly enhanced by, and requires integration of information concerning: 1. Pathogen life-cycle & epidemiology . Knowledge of pathogen structure, route of entry, interaction with cellular receptors, subsequent replication sites and disease-causing mechanisms are all important to identify antigens suitable for disease prevention. The demographics of infection, specific risk groups and age-specific infection rates determine which population to immunise, and at what age. 2. Immune control & escape . Interactions between the host and pathogen are explored, with determination of the relative importance of antibodies, T-cells of different types and innate immunity, immune escape strategies during infection, and possible immune correlates of protection. This information guides identification and selection of antigen and the specific immune response required for protection. 3. Antigen selection & vaccine formulation . The selected antigen is formulated to remain suitably immunogenic and stable over time, induce an immune response that is likely to be protective, plus be amenable to eventual scale-up to commercial production. 4. Vaccine preclinical & clinical testing . The candidate vaccine must be tested for immunogenicity, safety and efficacy in preclinical and appropriately designed clinical trials. This review considers these processes using examples of differing pathogenic challenges, including human papillomavirus, malaria, and ebola.